1992
DOI: 10.1046/j.1537-2995.1992.32392213803.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of serologically silent hepatitis B virus along with hepatitis C virus in two cases of posttransfusion hepatitis

Abstract: The polymerase chain reaction (PCR) was used to investigate the presence of hepatitis B virus (HBV)-related DNA sequences in blood from three blood donors and two transfusion recipients who developed posttransfusion non-A, non-B hepatitis (NANBH). In the first case, the sole donor was positive for antibody to hepatitis B surface (HBs) and core (HBc) antigens and had elevated alanine aminotransferase (ALT) levels, while the recipient had no HBV serologic markers. Both the donor and the recipient had serologic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…Occult HBV infection has received much attention recently, since it has been detected in patients with hepatocarcinoma [18], in blood donors and transfused patients [19,20], and in patients infected with hepatitis C virus [21][22][23]. In chronic HCV patients on hemodialysis, the prevalence of occult HBV infection is not yet well known [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…Occult HBV infection has received much attention recently, since it has been detected in patients with hepatocarcinoma [18], in blood donors and transfused patients [19,20], and in patients infected with hepatitis C virus [21][22][23]. In chronic HCV patients on hemodialysis, the prevalence of occult HBV infection is not yet well known [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…In antiHBc-positive patients, the prophylaxis with anti-HBV nucleos(t)ide analogues is indicated in hematopoietic stem cell transplantation and in onco-hematological diseases when high doses of corticosteroids and rituximab are used, whereas monitoring is indicated in all other clinical conditions or when rituximab-sparing schedules are used (Figure 2). The literature data have shown the efficacy of lamivudine in preventing HBV reactivation in these subsets of patients [17,43,61] . Also entecavir has been proposed in the prophylaxis of reactivation of OBI.…”
Section: Occult Hbv Infection In Hiv-positive Subjectsmentioning
confidence: 99%
“…OBI has also been described as a serological condition characterized by the presence of hepatitis B core antigen (anti-HBc) in the absence of HBsAg and anti-HBs (isolated anti-HBc) [7,[11][12][13][14][15] . OBI may be observed in the window period of acute HBV infection [16] in blood donors and in recipients of blood and blood products [9,17,18] , in patients with HCV chronic infection [7,19] , in cryptogenic chronic hepatitis, in patients under pharmacological suppression of the immune system [20,21] and in those with immunodepression due to HIV infection; it has also been associated to the development of hepatocellular carcinoma [22][23][24][25][26][27][28][29][30] . It has been shown that the hepatitis B virus maintains its pro-oncogenic properties in OBI [31] and that its presence in patients with chronic hepatitis C is associated with a higher risk of disease progression and HCC development [32][33][34][35][36] and with a reduced response to alfa interferon treatment [37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of complete infectious HBV particles in these patients was established using several complementary approaches: the transmission of hepatitis by HBV-DNA-positive sera into chimpanzees 13,14 ; post-transfusional and mother-tochild transmission of HBV DNA 14,15 ; the reinfection of liver grafts after liver transplantation for HBsAg-negative cirrhosis 16,17 ; and infection arising from HBsAg-negative organ donors. [18][19][20][21] These observations have been confirmed by reports of viral RNAs (including the viral pregenome) and covalently closed circular HBV DNA in the liver of these patients.…”
Section: What Is the Molecular Basis Of Hbv Persistence In Hbsag-negamentioning
confidence: 99%